Mycophenolate Mofetil (CellCept®) in Combination With Low Dose Prednisolone in Moderate to Severe Graves' Orbitopathy - Rajabi, Mohammad Taher; Rafizadeh, Seyed Mohsen; Mohammadi, Abbas; Eshraghi, Bahram; Mohammadi, Nader; Hosseini, Seyedeh Simindokht; Rajabi, Mohammad Bagher; Keshmirshekan, Mohammad Mohsen; Shahriari, Mansoor; Poursayed Lazarjani, Seyedeh Zahra; Parandin, Mohammad Mehdi (Frontiers in Medicine, 2022)
in this study, we aimed to investigate the efficacy of the combined use of mycophenolate mofetil (CellCept®) and low dose oral prednisolone in patients with moderate to severe Graves’ orbitopathy (GO). we investigated the relationship between TED-related parameters and proptosis reduction. In a prospective, nonrandomized, interventional case series, 242 patients with moderate-to-severe GO were, assigned to receive oral prednisolone (5 mg/ d) and mycophenolate mofetil (CellCept®) (one 500 mg tablet twice per day according to the therapeutic response). The patients monitored regularly during the 3rd, sixth, 12th and 18th month . The main outcome measures were the clinical activity score (CAS), intraocular pressure (IOP), diplopia, proptosis and visual acuity. The clinical response rate increased from 67.7 % on the third month to 89.2% on the sixth month, and 94.2% on the 12th month. This therapeutic response continued until the 18th month of follow-up. The CAS responses improved during our study: 70.6 % on the third month, 90.0% on the sixth month, and 92.5 % at 12th month. Proptosis improvement was 52 % on the third month, 71% on the sixth month, 83% on the 12th month, and 87.1% on the 18th month. Changes in IOP and visual acuity were not significant . The patient showed significant improvement in the Gorman score. A Shorter duration of treatment was seen in patients with earlier onset of intervention, younger age, and lack of all extraocular muscle (EOM) enlargement on computed tomography (CT) scan (p < 0.05). In addition, a better response (more reduction) in proptosis was related to: younger age at disease, earlier treatment intervention (less interval from the time the diagnosis of moderate-to-severe GO was made until medication initiation), shorter treatment time (interval from the the time the time the), less IOP, lack of EOM enlargement on CT scan, and lack of diplopia (P < 0.05). Adverse events occurred in six patients. Findings show that mycophenolate mofetil (CellCept®) plus low-dose prednisolone can be introduced as a new optimal dosing regimen in GO due to its better effect on chronic complications such as proptosis and diplopia.